Oldenlandia diffusa Extract Inhibits Biofilm Formation by Haemophilus influenzae Clinical Isolates - Wajima, Takeaki; Anzai, Yui; Yamada, Tetsuya; Ikoshi, Hideaki; Noguchi, Norihisa (PLOS ONE, 2016)
Oldenlandia diffusa has been empirically used as a therapeutic adjunct for the treatment of respiratory infections. To establish the basic evidence of its clinical usefulness, antimicrobial and biofilm inhibitory activities of an O. diffusa extract were examined against clinical isolates of Haemophilus influenzae, a major causative pathogen of respiratory and sensory organ infections. No significant growth inhibitory activity was observed during incubation for more than 6 h after the extract addition into a culture of H. influenzae. On the other hand, biofilm formation by H. influenzae, evaluated by a crystal violet method, was significantly and dose-dependently inhibited by the O. diffusa extract. Furthermore, the mRNA level of the biofilm-associated gene luxS of H. influenzae significantly decreased soon after the extract addition, and the suppressive effect continued for at least 2 h. At 2 h after the addition of the O. diffusa extract, the autoinducer in the culture supernatant was also significantly reduced by the O. diffusa extract in a dose-dependent manner. These results revealed that O. diffusa extract shows inhibitory activity against luxS-dependent biofilm formation but has no antimicrobial activity against planktonic cells of H. influenzae. Thus, O. diffusa extract might be useful as an adjunctive therapy for the treatment of respiratory infections caused by H. influenzae.